The Wonder wheel : Mae and June - Harper, Charise Mericle; Spires, Ashley, 1978- (Boston : Houghton Mifflin Harcourt, 2017)
June is happy to get a new neighbor, Mae, and soon the two of them are best friends and having adventures determined by the Wonder Wheel that they spin each morning.
Keywords: Best friends -- Fiction; Play -- Fiction; Imagination -- Fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Animals / Pets; JUVENILE FICTION / Fantasy & Magic